The Sociological Myth: A 1954 Controversy on Secularization Narratives. - Paul, Herman (Journal of Religion in Europe, 2016)
The term 'sociology' in 1950s theological discourse had connotations far beyond the field known as pastoral sociology. When in 1954 the Dutch theologian Henk Berkhof criticized "the sociological myth" that he saw permeating the churches in his country, at stake was not the legitimacy of pastoral sociology such as practiced by Wim Banning, among others, but the missionary priorities of churches in societies increasingly perceived as 'modern' and 'secular.' This article shows that, for Berkhof, 'sociology' was synonymous to a 'quantitative' mode of thinking that manifested itself most prominently in secularization narratives of a sort popularized by reform-oriented missionary theologians such as Hans Hoekendijk. A close reading of the debate following Berkhof's attack on "the sociological myth" reveals that 'sociology' served as shorthand for sustained attention to the questions and concerns of "modern men," which in turn presupposed a rather untraditional understanding of the relation between 'church' and 'world' as well as a historicist account of the relation between past and present.